Task-based language teaching for beginner-level learners of L2 French: An exploratory study - Erlam, R.; Ellis, Rod (2018)
This study investigated the effect of input-based tasks on the acquisition of vocabulary and grammar by beginner-level learners of L2 French and reported the introduction of task-based teaching as an innovation in a state secondary school. The experimental group (n = 19) completed a series of focused input-based language tasks, taught by their teacher, over two lessons. These tasks drew students' attention to markers of plurality in French. Students did not receive any explicit explanation of these features. Tests established that they acquired receptive knowledge of new vocabulary and target structures in comparison with a control group (n = 15) that completed the tests only. The teacher successfully implemented the tasks and considered the materials effective but also suggested improvements.